THE DEVELOPMENT OF AN ONLINE LESSON USING PROJECT-BASE LEARNING FOR WEBSITE DEVELOPMENT COURSE ON HTML WEBSITE DEVELOPMENT - สาลี, นิพรร (Pathumthani University Academic Journal, 2020)
The purpose of this research was to develop an online lesson using project based learning for website development course on HTML website development in the aspects as follow; 1) to develop an online lesson using project based learning to meet the efficiency standard of E1/E2 at 80/80, 2) to study the Effectiveness Index (E.I.) of the online lesson using project based learning, 3) to study the student’s satisfaction towards the online lesson using project based learning. The research sample was Matthayom 3 students of Triamudomsuksapattanakan, Bangkok. They were studying in the 1st semester of the academic year 2019. The research sample was selected by cluster sampling. There are 30 students from 1 class. The research instruments were 1) the online lesson using project based learning 2) pre-test and post-test 3) the questionnaire on the students’ satisfaction towards the online lesson. The statistics used in this research were mean ( ), percentage, and standard deviation (S.D.). The research about the development of an online lesson using project based learning for website development course on HTML website development that the researcher created found that when using the standard E1/E2 was at 80/80. It was equal to 83.21/82.89. It meets the standard. The Effectiveness Index (E.I.) of the online lesson was at .63. The satisfaction of students who learned from the online lesson using project based learning was at the highest level. The average was at 4.59. The standard deviation was at .53.